Pedagogical Impact of Extracurricular Activities on the Formation of Administrative Culture of Future Railway Transportation Engineers - Sushchenko, Roman (Pedagogical Discourse, 2016)
The article deals with the essence of pedagogical support and influence of extracurricular activities on the formation of administrative culture of future railway transportation engineers, the means of stimulating interest for administrative situations, using public dialogue for this purpose. In the article the urgency and pedagogical value of extracurricular work in shaping the future management culture of Transportation, because of its ineffective impact on the development of general culture and professionalism train graduates high school. Extracurricular work represents itself a share of university education, which in addition to teaching introduces significant component of cultural training, thus contributing to the development of management culture, integrity, civic engineer who hears the interests and views other than their own needs, he is always on the watch status procedure destroys the struggle between clans, groups, individuals, providing rational behavior and actions of all rational value, not creating tension around him more. Due to the fact that the formation of administrative culture of the future engineer is part of his professional role and importance of implementing the pilot program is guaranteed pedagogical and methodological provision of selected us for these important areas of extracurricular work: use of management culture in solving specific engineering problems; attract students to scientific justification means effective exposure management culture in the successful defense engineering innovations; demonstration identify highly modern management culture as an engineer in the production failed to overcome its administrative position managers and others. The importance of administrative culture in the renewal process of professional training, efficiency of individual techniques mechanism, including hardware, art techniques, especially communication techniques aimed at emotional interaction with a great number of students have been presented. We have considered such techniques as reference to personal experience, using flashbacks, reviving memories and personal reflection, shared search for truth, face-to-face conversation with students, encouraging students to talk about the most important, confidential aspects, stimulating shared sense of direction, dialogue with mass audiences, etc. Key words: extracurricular activities, professional training, formation, railway transportation engineer, interest, administrative culture.